Characterization of physicochemical and microbiological properties of gelatina blanca de pata de res (2019)
The gelatina blanca de pata de res (GBPR) is a typical handcrafted sweet, of which there is little scientific information. The aim of this research was to characterize the physicochemical and microbiological properties of GBPR, produced in Andalucia (Valle). The methodology was focused on the quantitative determination of these properties according to the Colombian law. The analyzed samples met the microbiological criteria. Escherichia coli and Staphylococcus aureus were not detected. However, statistically significant differences were found in the moisture, ash, total nitrogen and protein; as well as in the color parameters (L*, a*, b*). The obtained values of color difference (ΔE > 2.7) among samples provide confirmation that the procedures are not standardized. These results provide important contributions to the handcrafted food industry, highlighting the need to standardize the production and raw materials without compromising long lasting traditions.